2007
DOI: 10.1523/jneurosci.0599-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Bihemispheric Leftward Bias in a Visuospatial Attention-Related Network

Abstract: Asymmetry of spatial attention has long been described in both disease (hemispatial neglect) and healthy (pseudoneglect) states. Although right-hemisphere specialization for spatial attention has been suggested, the exact neural mechanisms of asymmetry have not been deciphered yet. A recent functional magnetic resonance imaging study from our laboratory serendipitously revealed bihemispheric left-hemifield superiority in activation of a visuospatial attention-related network. Nineteen right-handed healthy adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
77
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(98 citation statements)
references
References 38 publications
18
77
1
2
Order By: Relevance
“…In our data, cue and delay activation was more extensive in the right SMG than in the left. In the SPL, a bihemispheric leftward bias caused by right hemispheric dominance in the visuospatial network during passive fixation has been reported (35). Khonsari et al (36) found saccade preparatory signals (for left and right targets) only in the left PPC but found execution signals confined to the right PPC.…”
Section: Discussionmentioning
confidence: 95%
“…In our data, cue and delay activation was more extensive in the right SMG than in the left. In the SPL, a bihemispheric leftward bias caused by right hemispheric dominance in the visuospatial network during passive fixation has been reported (35). Khonsari et al (36) found saccade preparatory signals (for left and right targets) only in the left PPC but found execution signals confined to the right PPC.…”
Section: Discussionmentioning
confidence: 95%
“…The model proposed by Rueckert et al refers to a leftward attentional bias generated by spatial attention mechanisms located in the right hemisphere. This leftward attentional bias underlies most theories of pseudoneglect (Bultitude & Aimola-Davies, 2006;Nicholls & Roberts, 2002) and the neural/cognitive models that underlie them (Siman-Tov et al, 2007;Thiebaut de Schotten et al, 2011). Rueckert et al (2002) also discussed the relative under-and overestimations of lines of different lengths.…”
Section: Discussionmentioning
confidence: 96%
“…As a result, the act of spatial processing during line bisection precipitates a bias of attention to the left hemispace, causing the features of the stimulus on that side to appear more salient. More recent models have proposed a revised activation-orientation model, in which pseudoneglect and neglect are explained in terms of asymmetric interhemispheric neural activation and connectivity (Siman-Tov et al, 2007). Neuroanatomical support for these models has come from a diffusion tensor-imaging study by Thiebaut de Schotten et al (2011), which showed that individual differences in the strengths of pseudoneglect were related to asymmetries in the neural pathways connecting the ventral and dorsal attentional systems in the right hemisphere.…”
mentioning
confidence: 99%
“…As the task used in the current study required simple button press responses and keyboard responses evoke a minimal amount of motor movement (i.e., McCourt & Olafson, 1997), pre-motor and motor biases do not provide an adequate explanation for the leftward bias either. Lateral asymmetries in cerebral activation are suggested to underlie the leftward bias (Schiff & Truchon, 1993), as the right hemisphere is primarily responsible for spatial attention (Corbetta et al, 1995;Posner & Petersen, 1990;Siman-Tov et al, 2007, but c.f. Giesbrecht, Kingstone, Handy, Hopfinger, & Mangun, 2006.…”
Section: Discussionmentioning
confidence: 99%
“…As the right hemisphere, specifically the posterior parietal area, is primarily responsible for spatial attention (e.g., Corbetta et al, 1995;Posner & Petersen, 1990;Posner & Rothbart, 2007), attention is preferentially directed toward the left side of space. This suggestion has been supported by neuroimaging data demonstrating that visuospatial attention networks are more activated by information in the left VF (Siman-Tov et al, 2007). Further, neuroimaging data indicate that the right hemisphere is more active during line bisection and landmark tasks (Bjoertomt et al, 2002;Çiçek et al, 2009;Fink et al, 2000;Fink et al, 2001;Foxe et al, 2003).…”
Section: Introductionmentioning
confidence: 87%